Role of Neutrophils in the Development of Steatotic Liver Disease - Choi, You-Jin; Kim, Yeonsoo; Hwang, Seonghwan (Seminars in Liver Disease, 2024)
This review explores the biological aspects of neutrophils, their contributions to the development of steatotic liver disease, and their potential as therapeutic targets for the disease. Although alcohol-associated and metabolic dysfunction-associated liver diseases originate from distinct etiological factors, the two diseases frequently share excessive lipid accumulation as a common contributor to their pathogenesis, thereby classifying them as types of steatotic liver disease. Dysregulated lipid deposition in the liver induces hepatic injury, triggering the activation of the innate immunity, partially through neutrophil recruitment. Traditionally recognized for their role in microbial clearance, neutrophils have recently garnered attention for their involvement in sterile inflammation, a pivotal component of steatotic liver disease pathogenesis. In conclusion, technological innovations, including single-cell RNA sequencing, have gradually disclosed the existence of various neutrophil subsets; however, how the distinct subsets of neutrophil population contribute differentially to the development of steatotic liver disease remains unclear.
Keywords: neutrophil; steatosis; alcohol-associated liver disease; metabolic dysfunction-associated liver disease